Complete nucleotide sequence and genome organization of bovine parvovirus. - Chen, K C (1986)
We determined the complete nucleotide sequence of bovine parvovirus (BPV), an autonomous parvovirus. The sequence is 5,491 nucleotides long. The terminal regions contain nonidentical imperfect palindromic sequences of 150 and 121 nucleotides. In the plus strand, there are three large open reading frames (left ORF, mid ORF, and right ORF) with coding capacities of 729, 255, and 685 amino acids, respectively. As with all parvoviruses studied to date, the left ORF of BPV codes for the nonstructural protein NS-1 and the right ORF codes for the major parts of the three capsid proteins. The mid ORF probably encodes the major part of the nonstructural protein NP-1. There are promoterlike sequences at map units 4.5, 12.8, and 38.7 and polyadenylation signals at map units 61.6, 64.6, and 98.5. BPV has little DNA homology with the defective parvovirus AAV, with the human autonomous parvovirus B19, or with the other autonomous parvoviruses sequenced (canine parvovirus, feline panleukopenia virus, H-1, and minute virus of mice). Even though the overall DNA homology of BPV with other parvoviruses is low, several small regions of high homology are observed when the amino acid sequences encoded by the left and right ORFs are compared. From these comparisons, it can be shown that the evolutionary relationship among the parvoviruses is B19 in equilibrium with AAV in equilibrium with BPV in equilibrium with MVM. The highly conserved amino acid sequences observed among all parvoviruses may be useful in the identification and detection of parvoviruses and in the design of a general parvovirus vaccine.